Hubungan Lama Waktu Operasi Dengan Kecemasan Keluarga Pasien Operasi Elektif Bedah Anak Di Instalasi Bedah Sentral Rsud Dr. Saiful Anwar Malang - Asih, Hutpri Swasti; Febriani, Reny Tri; Sari, Nining Loura; Trigantara, Regista (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: This research aimed to analyze the relationship between the length of operation time and the anxiety of the families of pediatric elective surgery patients at the Central Surgical Installation of RSUD Dr. Saiful Anwar Malang. Methods: The research method in this study uses a descriptive analytical design with a cross-sectional approach. The sample for this study was the families of patients who underwent elective pediatric surgery at the Central Surgical Installation of RSUD Dr. Saiful Anwar Malang. As many as 37 respondents were selected using the total sampling. The instruments used were the Hamilton Rating Scale for Anxiety (HARS) to measure family anxiety and an observation sheet to assess the length of operation time. Results: This study show that almost half of the patient's families have a moderate level of anxiety with a moderate level of operating time (60 – 180 minutes). The Spearman Rank test show a significant relationship between the length of operation time and the anxiety of the families of elective surgery patients for pediatric surgery patients at the Central Surgery Installation of RSUD Dr. Saiful Anwar Malang (p-value 0.000; r: 0.841). Conclusion: The long duration of surgery causes parents to worry because they think about the complexity of the surgical procedure and the increased risk of surgery for the child. It is hoped that this research can be a study for nurses and hospitals regarding the management of anxiety in the families of patients undergoing elective pediatric surgery with a long surgical duration.